MEDICAL AND PREVENTIVE OPPORTUNITIES OF THE NEW GOAT MILK BASED FOODSTUFFS FOR CHILDREN - O.A. Matalygina ("Paediatrician" Publishers LLC, 2008)
The article gives chemical and biological characteristics of the goat milk and adapted formulas based thereupon (MD MIL Kozochka 1 and MD MIL Kozochka 2). The author also considers their medical and preventive opportunities.Key words: goat milk, children's feeding, food allergy.